Customised Enriched Coconut Oil as Panacea for Oral Biofilm Mediated Diseases - A Prospective Study - Shamini Sai; Raga T Nivedha; Srinivasan Narasimhan; Aruna K. Veronica; Jayaraman Selvakumar; Anand V. Susila (Indian Journal of Dental Research)
Aims: To evaluate a customised enriched formulation of coconut (CEC) oil with Arimedadi Tailam (AT) and 0.2% chlorhexidine mouth rinse (CHX) for their plaque control and potential anticaries effects using the oratest in healthy volunteers. Settings and Design: Parallel, double-blinded (outcome assessor and statistician), randomised controlled institution-based pilot study. Methods and Materials: 60 adults (18-22 years) having DMFT score of 2-11, gingival and plaque index as zero, no history of antibiotics for one month or fluoride application in 2 weeks were randomly divided (computer-generated list) and allocated into 3 groups (A-CHX, B-CEC, C-AT) of 20 subjects each based on the intervention. Oratest at baseline, days 15 and 30 were recorded. Statistical Analysis Used: Due to 5 dropouts on day 30, data were analysed based on the intention-to-treat (ITT) approach. The difference in oratest scores (baseline vs. day 15 and 30) were found to be normally distributed (Shapiro-Wilk test and Levene's test). One way ANOVA followed by Tukey's post hoc test was used to determine the statistically significant difference (P < 0.05) between groups. Results: Plaque and gingival index was zero throughout the study period. Difference in oratest scores was highest with CEC oil, followed by CHX and AT though there was no statistically significant differences between groups at baseline vs day 15 (P = 0.203) and baseline vs day 30 (P = 0.085) and between oils from baseline vs day 30 (P = 0.068). Conclusions: Within the limitations of the pilot study, both oils are comparable to CHX for their antiplaque and anticaries potential. Clinically, CEC was better than AT though statistical difference was not there.